Ectopic Parathyroid Glands and their Anatomical, Clinical and Surgical Implications - Noussios, G.; Anagnostis, P.; Natsis, K. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Ectopic parathyroid glands result from aberrant migration during early stages of development and lack of successful identification may lead to lack of success in parathyroid surgery. They constitute a common etiology of persistent or recurrent hyperparathyroidism, when they are missed at initial diagnosis. Their prevalence is about 2–43% in anatomical series and up to 16% and 14% in patients with primary and secondary hyperparathyroidism, respectively. Ectopic inferior parathyroids are most frequently found in the anterior mediastinum, in association with the thymus or the thyroid gland, while the most common position for ectopic superior parathyroids is the tracheoesophageal groove and retroesophageal region. Neck ultrasound and 99mTc Sestamibi scan are first-line imaging modalities, although with low sensitivity and specificity. However, their combination with modern techniques, such as single photon emission computed tomography (SPECT) alone or in combination with CT (SPECT/CT) increases their diagnostic accuracy. Fine needle-aspiration cytology of a lesion suspicious for parathyroid tissue and measurement of parathyroid hormone (PTH) in the aspired material further assist to the successful preoperative localization of ectopic glands. Common sites for surgical investigation are the upper thyroid pole and the upper vascular thyroid stalk behind the hypopharynx and cervical esophagus for the superior parathyroids, and the carotid artery bifurcation and the thymic tongue, for the inferior parathyroids. Radioguided minimally invasive parathyroidectomy after successful localization, assisted by rapid PTH measurement postoperatively, significantly improves surgical outcomes in patients with ectopic parathyroid adenomas.
Keywords: primary hyperparathyroidism; ectopic parathyroid; parathyroidectomy; supernumerary parathyroids